Organic reductants based leaching: A sustainable process for the recovery of valuable metals from spent lithium ion batteries. (May 2018) - Chen, Xiangping; Guo, Chunxiu; Ma, Hongrui; Li, Jiazhu; Zhou, Tao; Cao, Ling; Kang, Duozhi
Highlights: Cellulose, sucrose and glucose are used as green reductants during the leaching reactions. Sucrose and glucose show better reduction performance over cellulose. Over 95% of Co and Li can be recovered using sucrose and glucose as reductant. A tentative exploration of reduction mechanism has been proposed for different reductants. Abstract: It is significant to recover metal values from spent lithium ion batteries (LIBs) for the alleviation or prevention of potential risks towards environmental pollution and public health, as well as for the conservation of valuable metals. Herein a hydrometallurgical process was proposed to explore the possibility for the leaching of different metals from waste cathodic materials (LiCoO2 ) of spent LIBs using organics as reductant in sulfuric acid medium. According to the leaching results, about 98% Co and 96% Li can be leached under the optimal experimental conditions of reaction temperature - 95 °C, reaction time - 120 min, reductive agent dosage - 0.4 g/g, slurry density - 25 g/L, concentration of sulfuric acid-3 mol/L in H2 SO4 + glucose leaching system. Similar results (96% Co and 100% Li) can be obtained in H2 SO4 + sucrose leaching system under optimized leaching conditions. Despite a complete leaching of Li (∼100%), only 54% Co can be dissolved in the H2 SO4 + cellulose leaching system under optimized leaching conditions. Finally, different characterization methods, including UV–Vis, FT-IR, SEM and XRD, were employed for the tentative exploration of reductive leaching reactions using organic as reductant in sulfuric acid medium. All the leaching and characterization results confirm that both glucose and sucrose are effective reductants during leaching, while cellulose should be further degraded to organics with low molecular weights to achieve a satisfactory leaching performance.